ADSORPTION MALACHITE GREEN ON NATURAL ZEOLITE - Eko Ariyanto (Dept. of Chemical Engineering, Diponegoro University, 2009)
A natural zeolite was employed as adsorbent for reducing of malachite green from aqueous solution. A batch system was applied to study the adsorption of malachite green in single system on natural zeolite. The adsorption studies indicate that malachite green in single component system follows the second-order kinetics and the adsorption is diffusion process with two stages for malachite green. Malachite green adsorption isotherm follows the Langmuir model.